Mechanics of composite structures - Kollar, L. Peter 1926-2000 (Cambridge University Press, 2003)
An increase in the use of composite materials has led to a greater demand for engineers versed in the design of structures made from such materials. This book demonstrates advanced concepts and emphasizes structures. More than 300 illustrations, 50 fully worked problems, and material properties data sets are included.
Keywords: Composite materials -- Mechanical properties.; elektronické knihy; electronic books